Health related quality of life, depression and climacteric symptoms in women from a low-income community - Dedicação, Anny Caroline; Avila, Mariana Arias; Saldanha, Maria Elisabete Salina; Moccellin, Ana Silvia; Sato, Tatiana de Oliveira; Driusso, Patricia (Revista Kairós-Gerontologia, 2019)
Purpose: To evaluate health-related quality of life, depressive and climacteric symptoms in Southeastern low-income community-dwelling climacteric women from Brazil. Methods: A comparative cross-sectional study. Outcome measures were quality of life, depression and climacteric symptoms. Results and conclusion: Participants presented impaired quality of life, and an expressive number of them presented moderate and severe depression and moderate severity climacteric symptoms.